2022
DOI: 10.1177/03331024221120054
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in cluster headache: A hospital-based study in Taiwan

Abstract: Objectives To compare the clinical profiles between male and female cluster headache patients from a large cohort. Methods This hospital-based study enrolled patients diagnosed with cluster headache between 1997 to 2021. Participants completed structured questionnaires collecting information on demographics, clinical profiles, and quality of life. Treatment regimens and effectiveness were determined through medical chart review. All variables were compared between the sexes. Results In total, 798 patients (M/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 45 publications
(133 reference statements)
3
27
1
Order By: Relevance
“…An Italian study reported a decline in the M:F ratios from 6.2:1 to 2.1:1 according to onset (before 1960 vs. the 1990s) (53,54). A large cohort study in Taiwan also reported a decline in the M:F ratio from 5.2:1 to 4.3:1 according to the time of enrolment (1997–2020 vs. 2011–2021) (35). The M:F ratios reported in studies in Germany decreased from 4.3:1 in 1988 to 2.1:1 in 2021 (39,57,58) and, in France, decreased from 4.7:1 in 2002 to 1.7:1 in 2008 (56,59).…”
Section: Clinical Spectrum Of Chmentioning
confidence: 99%
See 4 more Smart Citations
“…An Italian study reported a decline in the M:F ratios from 6.2:1 to 2.1:1 according to onset (before 1960 vs. the 1990s) (53,54). A large cohort study in Taiwan also reported a decline in the M:F ratio from 5.2:1 to 4.3:1 according to the time of enrolment (1997–2020 vs. 2011–2021) (35). The M:F ratios reported in studies in Germany decreased from 4.3:1 in 1988 to 2.1:1 in 2021 (39,57,58) and, in France, decreased from 4.7:1 in 2002 to 1.7:1 in 2008 (56,59).…”
Section: Clinical Spectrum Of Chmentioning
confidence: 99%
“…alcohol consumption or smoking) have been suggested as the cause of changes in the M:F ratios, as a recent genome-wide association study revealed smoking as a causal risk factor of CH (33). However, a Taiwanese study showed that the M:F ratio of current smokers increased from 14.9:1 to 21.6:1 in patients diagnosed before and after 2010, respectively (35). Another explanation is that CH could have been more frequently misdiagnosed in women in the earlier days.…”
Section: Clinical Spectrum Of Chmentioning
confidence: 99%
See 3 more Smart Citations